Spectrophotometric Determination of Mycophenolate Mofetil as Its Charge-Transfer Complexes with Two π-Acceptors - K. B. Vinay; H. D. Revanasiddappa; M. S. Raghu; Sameer. A. M. Abdulrahman; N. Rajendraprasad (Journal of Analytical Methods in Chemistry)
Two simple, selective, and rapid spectrophotometric methods are described for the determination of mycophenolate mofetil (MPM) in pure form and in tablets. Both methods are based on charge-transfer complexation reaction of MPM with p-chloranilic acid (p-CA) or 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) in dioxane-acetonitrile medium resulting in coloured product measurable at 520 nm (p-CA) or 580 nm (DDQ). Beer’s law is obeyed over the concentration ranges of 40–400 and 12–120 μg mL−1 MPM for p-CA and DDQ, respectively, with correlation coefficients (r) of 0.9995 and 0.9947. The apparent molar absorptivity values are calculated to be 1.06×103 and 3.87×103 L mol−1 cm−1, respectively, and the corresponding Sandell’s sensitivities are 0.4106 and 0.1119 μg cm−1. The limits of detection (LOD) and quantification (LOQ) are also reported for both methods. The described methods were successfully applied to the determination of MPM in tablets. Statistical comparison of the results with those of the reference method showed excellent agreement. No interference was observed from the common excipients present in tablets. Both methods were validated statistically for accuracy and precision. The accuracy and reliability of the methods were further ascertained by recovery studies via standard addition procedure.